Bond reactivity indices approach analysis of the [2+2] cycloaddition of jatrophane skeleton diterpenoids from Euphorbia gaditana Coss to tetracyclic gaditanone. (December 2020) - Flores-Giubi, M. Eugenia; Botubol-Ares, Jose Manuel; Durán-Peña, María J.; Escobar-Montaño, Felipe; Zorrilla, David; Sánchez-Márquez, Jesús; Muñoz, Eduardo; Macías-Sánchez, Antonio J.; Hernández-Galán, Rosario
Abstract: The reaction mechanism of the intramolecular [2 + 2] cycloaddition from a jatrophane precursor to the gaditanane skeleton, an unprecedented 5/6/4/6-fused tetracyclic ring framework recently isolated from Euphorbia spp., was studied using the bond reactivity indices approach. Furthermore, six diterpenoids, including three undescribed jatrophanes isolated from E. gaditana Coss, were described. The structures of these compounds were deduced by a combination of 2D NMR spectroscopy and ECD data analysis. Graphical abstract: Image 1 Highlights: Three undescribed jatrophanes were isolated from Euphorbia gaditana Coss. Biosynthesis of gaditanane skeleton was studied by bond reactivity indices approach. An intramolecular [2 + 2] cycloaddition of a jatrophane gives gaditanane skeleton.